2003
DOI: 10.1079/joh2003189
|View full text |Cite
|
Sign up to set email alerts
|

Local variation in helminth burdens of Egyptian spiny mice (Acomys cahirinus dimidiatus) from ecologically similar sites: relationships with hormone concentrations and social behaviour

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. AbstractPopulations of Egyptian spiny mice (Acomys cahirinus dimidiatus) in a fragmented montane wadi system in the Sinai showed significant differences in the abundance of gut helminth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Such differences might lead to local adaptation of mice to their prevailing parasite fauna, a phenomenon that appears to be taking place in relation to androgen metabolism and intra‐specific social behaviour in Ac. dimidatus populations (Barnard et al , 2003 b ). Indeed, it may be the case that populations of mice within wadis (which are usually associated with Bedouin gardens) are locally specialized to a particular parasite fauna.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such differences might lead to local adaptation of mice to their prevailing parasite fauna, a phenomenon that appears to be taking place in relation to androgen metabolism and intra‐specific social behaviour in Ac. dimidatus populations (Barnard et al , 2003 b ). Indeed, it may be the case that populations of mice within wadis (which are usually associated with Bedouin gardens) are locally specialized to a particular parasite fauna.…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier papers (Behnke et al , 2000, 2004; Barnard et al , 2003 b ), we referred to the host spiny mouse as Acomys cahirinus dimidiatus . Here we refer to the host as Ac.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…have been examined for endoparasites by several authors, who reported mostly cestodes and oxyurid nematodes (Hussein and Kalantan 1993;Behnke et al 2000;Barnard et al 2003). Only a single Eimeria species, E. cahirinensis Couch, Blaustein, Duszynski, Shenbrot andNevo, 1997 (Couch et al 1997), identified on the basis of oocyst morphology, has been reported from these hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Such conditions also could affect social interactions that, in turn, can affect social structure. Among the most likely mechanisms linking stress response and fitness are the effects on the cellular and humoral ability to mount an immune response against pathogens (Keita et al 2007; Ndong et al 2007), which in turn influences parasite infection (Barnard et al 1998, 2003) and resistance (Kiank et al 2006; Morales et al 2006; Smith et al 1996; but see Barnard et al 2003). Research aimed at determining the links between stressors such as parasitism, the stress response, and fitness would increase our understanding of the evolutionary significance of intra- and interspecific variation in sociality in caviomorphs.…”
Section: Behavioral Endocrinologymentioning
confidence: 99%